SKEPTISME PROFESIONAL SEBAGAI VARIABEL INTERVENING HUBUNGAN KOMPETENSI AUDITOR, TEKANAN WAKTU DAN KEAHLIAN FORENSIK TERHADAP KEMAMPUAN AUDITOR MENDETEKSI KECURANGAN - Prasetya, Arnando; Afrizal; Putra, Wirmie Eka (Jurnal Akuntansi Trisakti, 2023)
This study aims to examine the effect of auditor’s competence, time pressure, and forensic expertise on the auditor's ability to detect fraud with professional skepticism as an intervening variable. This research was conducted at the Financial and Development Supervisory Agency (BPKP) Jambi Provincial Representative. The sampling technique in this study uses a saturated sampling technique. The data in this study is quantitative primary data, which was collected through the distribution of questionnaires to auditors at the Financial and Development Supervisory Agency (BPKP) Jambi Provincial Representative. The analysis technique used is Partial Least Square-Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 3.2.9 software. The results of this study found that (1) auditor’s competence and time pressure have a significant effect on the auditor's ability to detect fraud and professional skepticism, (2) forensic expertise does not have a significant effect on the auditor's ability to detect fraud but has a significant effect on professional skepticism, (3) professional skepticism does not have a significant effect on the auditor's ability to detect fraud. As for the effect of professional skepticism as mediating variable, it was found that (4) competence, time pressure and forensic expertise did not have a significant effect on the auditor's ability to detect fraud through professional skepticism.